The Way Of Narrative On The Novel Qinqiang - Qi, Mo; Yingfang, Zhang (Lingua Cultura, 2011)
Jiapingao’s novel QINQIANG is paid attention to by some experts recently because of the way of narrative. It is made up by 3 parts: primitive and life-streaming composition；the way of separated-perspective, the moving perspective,imagism；the development of narrative perspective. All these make Jia’s novel more perfect and unique. The way to study the novel is to use narrative theories, cultural analysis and close reading. In a word,Jia’s ways of narrretive in his novel QINQIANG has been in a new highland in China.